The Readiness of B40 Sabah Rural Students to Enter University: A Preliminary Overview - Joki Perdani Sawai; Habibie Ibrahim; Nurul Hudani Md Nawi; Risalshah Latif; Siew Nyet Moi @ Sopiah Abdullah; Fazley Andi Sofian (Southeast Asia Psychology Journal, 2023)
This paper reports the results of a preliminary study and tries to examine the question of whether poverty in the family has a negative effect and becomes an obstacle for children and whether the children are prepared from all aspects (psychological, emotional, economic and mental) to enter the university world. Entering university is the dream of most people, both students and parents. However, the dream of entering university is not so easy for some B40 students and families. This study is a preliminary survey study of students among rural B40 families in the state of Sabah. Study participants are students who have been on campus and are currently studying at the university. They consist of 1st-3rd year students at the Faculty of Psychology and Education, UMS. A qualitative approach is used which is the focus group interview method. Data were analyzed using thematic analysis. The results of the study show that there are two categories of students, namely students who; i) really intend to enter the university world and; ii) students who do not intend to enter the university world. Both categories of students have reasons why they intend and do not intend to enter university as reported in this paper. In addition, an interesting finding was reported that there was a difference in family support for boys and girls in the process of children pursuing their ambitions to continue their studies at the university level. The results of this study are expected to support policy makers in helping the poor and B40 families to achieve change in themselves, families and society through achievement in education.